Inkjet manipulated homogeneous large size perovskite grains for efficient and large-area perovskite solar cells. (April 2018) - Li, Pengwei; Liang, Chao; Bao, Bin; Li, Yanan; Hu, Xiaotian; Wang, Yang; Zhang, Yiqiang; Li, Fengyu; Shao, Guosheng; Song, Yanlin
Abstract: The performance of large-area perovskite solar cells (PSCs) is confined to the non-uniformity edge-coating and crystalline defects. Focusing on the critical requirement of large-area uniform and compact crystallized perovskite film for efficient PSCs, here, an inkjet manipulated approach is introduced for controlling the thin-film perovskite growth in a mesoporous solar cell device structure. The ink droplet wetting behavior on mesoporous substrate, the physical properties of solutions have been systematically investigated. Uniform liquid membrane was obtained via precisely controlled micro-droplets by inkjet-printing. Mesoporous substrates guarantee fast and complete coalescence of the precursor droplets, and limit random diffusion of the precursor solution. Homogeneous PbI2 film leads to a compact perovskite film with micro-scale crystalline grains, which enables PSCs high power conversion efficiencies (PCEs) of 18.64% for small area (0.04 cm 2 ) and 17.74% for large area (2.02 cm 2 ). The enhanced performance can be ascribed to improved uniformity of the perovskite film morphology, favorable perovskite crystallite orientation, large grain size (> 2 µm) and less grain boundaries. Inkjet manipulation provides a facile approach to fabricate large-area and high-quality films for future optoelectronics, including field effect transistors, light-emitting diodes, and sensor devices. Graphical abstract: fx1 Highlights: Adjusting the properties of the printed solvent and the substrate can achieve uniform and large perovskite grains. Large perovskite grain sizes helps to improve the photovoltaic performance of perovskite solar cells. Over 2 cm 2 of perovskite solar cell with the power conversion efficiency of 17.74% via inkjet printing.